Aspects of the importance of using a NATO standard individual first aid kit in wartime - Tverdokhliebova, N. Ye.; Yevtushenko, Nataliia (Український державний університет імені Михайла Драгоманова, 2024)
Wartime is always accompanied by significant risks to the life and health of the military and civilians. One of the key factors that ensure successful care and rescue of the wounded is properly equipped NATO-standard medical kits.
Keywords: digital technologies; risks; individual first aid kit; NATO standard